Rules on the Web: From Theory to Applications 8th International Symposium, RuleML 2014, Co-located with the 21st European Conference on Artificial Intelligence, ECAI 2014, Prague, Czech Republic, August 18-20, 2014, Proceedings - Bikakis, Antonis.; Bikakis, Antonis.; Fodor, Paul.; Fodor, Paul.; Roman, Dumitru.; Roman, Dumitru. (Programming and Software Engineering ;, 2014)
This book constitutes the refereed proceedings of the 8th International RuleML Symposium, RuleML 2014, co-located with the 21st European Conference on Artificial Intelligence, ECAI 2014, held in Prague, Czech Republic, in August 2014. The 17 full and 6 short papers presented together with 3 keynote talks were carefully reviewed and selected from 48 submissions. The papers cover the following topics: semantic web rule languages and standards, rule engines, formal and operational semantics and rule-based systems, the relation between natural language and rules, automation of business rules generation from existing data, and aspects related to legal rules and norms for web and corporate environments.